2007
DOI: 10.1080/10168730701345414
|View full text |Cite
|
Sign up to set email alerts
|

Export-led Growth in South Asia: A Panel Cointegration Analysis

Abstract: In this paper, we attempt to examine the export-led and manufacturing export-led growth hypothesis for four South Asian Countries; namely, India, Pakistan, Bangladesh and Sri Lanka, using Pedroni's panel cointegration technique for the period 1980-2002. In this context we estimate growth accounting equations to investigate the impact of exports, manufacturing exports and other important physical and human capital variables on both total GDP and non-export GDP. The study finds long-run equilibrium relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(21 citation statements)
references
References 43 publications
2
18
1
Order By: Relevance
“…Micro findings are consistent with Abu-Quarn and Abu-Bader (2004), Kurt and Terzi (2007), and Yaprakli (2007) who conclude that the export-led growth hypothesis is found to be valid in the manufacturing sector of Turkey. Moreover, in the manufacturing industry findings are consistent with Parida and Sahoo (2007), Ghatak et al (1997), Herzer et al (2006), Cuerasma and Wörz (2005), Cipamba (2012), Shakouri and Yazdi (2012), and Shafiullah et al (2017) in the case of countries other than Turkey. In the case of the fishery sector, findings of this study have results consistent with those by Duc and Tram (2011) in Vietnam.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Micro findings are consistent with Abu-Quarn and Abu-Bader (2004), Kurt and Terzi (2007), and Yaprakli (2007) who conclude that the export-led growth hypothesis is found to be valid in the manufacturing sector of Turkey. Moreover, in the manufacturing industry findings are consistent with Parida and Sahoo (2007), Ghatak et al (1997), Herzer et al (2006), Cuerasma and Wörz (2005), Cipamba (2012), Shakouri and Yazdi (2012), and Shafiullah et al (2017) in the case of countries other than Turkey. In the case of the fishery sector, findings of this study have results consistent with those by Duc and Tram (2011) in Vietnam.…”
Section: Discussionsupporting
confidence: 74%
“…In line with the theory which extended Neoclassical production function with foreign trade and empirical literature (see, for example : Feder 1982;Baldwin 1992;Ben-David and Loewy 2003;Gundlach 2007;Parida and Sahoo 2007;Awokuse 2008;Kristjanpoller and Olson 2014), economic growth (y) is defined as a function of physical capital (k), labour (l) and exports (x):…”
Section: Model and Datamentioning
confidence: 98%
“…Recognizing the omitted variable bias, the author suggested a closer look at other important variables that may explain economic growth in Malaysia. Mahadevan (2007) used the Toda and Yamamoto (1995) causality test and found evidence of two-way causality between exports and trade-adjusted GDP in Malaysia for the period 1974-2003. Parida and Sahoo (2007 examined the impact of exports on both total GDP and non-export GDP on four South Asian countries, namely, India, Pakistan, Bangladesh and Sri Lanka.…”
Section: Introductionmentioning
confidence: 99%
“…Reppas and Christopoulos (2005) also found evidence supporting the growth-led export and not the export-led growth hypothesis for Cote d'Ivoire, Gabon, South Africa, Malaysia, and Pakistan. In the case of Pakistan, Love and Chandra (2004); Shirazi and Manap (2005); Parida and Sahoo (2007) and Shahbaz et al (2011) confirmed the export-led growth hypothesis, while Bahmani-Oskooee (1993); Khan and Saqib (1993) and Saleem and Sial (2015) found bidirectional causal relationship between exports and output, and Dodaro (1993), Afzal and Hussain (2010) and Kumari and Malhotra (2015) found no causal relationship between exports and economic growth. For Malaysia, Islam (1998) did not find any causal relationship between exports and economic growth, while Al-Yousif (1999); Ekanayake (1999) and Choong et al (2005) provided evidence confirming the export-led growth hypothesis, and Hassan and Murtala (2016) found evidence validating the growth-led export hypothesis.…”
Section: Introductionmentioning
confidence: 90%